Association of new generation anti-CCP antibodies with disease severity and functional status in rheumatoid arthritis patients - Azalan, Maryam Syahidah; Wan Mohamad, Wan Majdiah; Saddki, Norkhafizah; Wan Ghazali, Wan Syamimee (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2023)
Introduction: Detection of anti-cyclic citrullinated peptide (anti-CCP) antibodies in patients with rheumatoid arthritis (RA) is associated with higher disease activity and lower functional ability. This study investigated the presence of the new generation of anti-CCP antibodies (anti-CCP2 IgG, anti-CCP2 IgA and anti-CCP3.1 IgG/IgA) and their association with disease severity and functional status of RA patients. Methods: A total of 46 RA patients and 40 healthy controls participated in this cross-sectional study that was conducted at the Rheumatology Clinic, Hospital Universiti Sains Malaysia. Blood samples were taken from all participants for anti-CCP2 IgG, anti-CCP2 IgA, and anti-CCP3.1 IgG/IgA analysis. Disease severity and functional status of RA patients were measured using the Disease Activity Score-28 (DAS28) and the modified Health Assessment Questionnaire (mHAQ) respectively. Results: Significantly higher proportion of RA patients were found with positive anti-CCP2 IgG (63.0%), anti-CCP2 IgA (37.0%), and anti-CCP3.1 IgG/IgA antibodies (63.0%) than the healthy controls. No significant association was found between anti-CCP antibodies status and mean DAS28 score of the RA patients. However, RA patients with negative anti-CCP2 IgG status had higher mean mHAQ score than patients with positive anti-CCP2 IgG status. Conclusion: Our study has demonstrated detection of the new generation anti-CCP antibodies in RA patients, supporting the use of autoantibodies in RA diagnosis. While no significant association was found between the presence of anti-CCP antibodies and disease severity of RA patients, the absence of anti-CCP2 IgG was associated with worse function and greater disability of the patients.